Qia’erdunbasixi Fe–Cu Deposit in Sawur, Xinjiang: A Case Study of Skarn Deposit Hosted by Volcanic Rock - Yang, Shuang; Zhou, Qiu-Shi; Wang, Rui; Zhu, Yongfeng (Frontiers in Earth Science, 2022)
The Sawur Cu-Au belt, northern Xinjiang, China, is the eastward extension of the Zarma-Sawur Cu-Au belt in Kazakhstan. Late Paleozoic volcanic rocks and intrusions are highly developed in Sawur. Qia’erdunbasixi Fe-Cu deposit in Sawur is a newfound deposit, still in exploration. Wall rocks consist of andesite and minor basalt and tuff, which belong to calc-alkaline series with large ion lithophile elements (LILE) enrichment, high LREE/HREE fractionation and high field strength elements (HFSE) depletion. These are typical characteristics of island arc volcanic rocks. The U-Pb SHRIMP zircon age of Qia’erdunbasixi syenite intruding into the volcanic rocks is 345 ± 2.2 Ma (MSWD=1.3), presenting as the lower limit of skarn Fe mineralization. The initial 87Sr/86Sr ratios of Qia’erdunbasixi syenite range from 0.70403 to 0.70420, and εNd(t) values are from +5.5 to +6.8, these samples exhibit the arc magma characteristics. Diorites with similar REE features with syenite should share the same magma source. Magnetite and copper mineralization develop mostly along the contacts of syenite and diorite, respectively. Fe mineralization develops along the contact of syenite, with typical skarn zonation. Metallogenesis event could be divided into early skarn stage (Diopside-Augite-Andradite-Magnetite-Calcite-Quartz), late skarn stage (Epidote-Chlorite-Actinolite-K-feldspar-Calcite-Magnetite-Quartz) and hydrothermal stage (Quartz-Magnetite-K-feldspar-Calcite-Sercite-Chlorite-Actinolite-Prehnite-Chalcopyrite -Pyrite). The early-mid stage magnetite with certain amounts of Ti and V is crystallized from magma, while the late stage magnetite has typical characteristics of hydrothermal calcic skarn magnetite. The temperature of mineralization is among 350-450 ℃ based on mineral assemblages and phase diagrams. Copper mineralization is concentrated along the outer contact of diorite. Paragenesis sequences of four stages of mineralization could be identified for copper mineralization: (1) Albite-Quartz; (2) Chalcopyrite-Pyrite-Gold-Seriate-Quartz; (3) Chalcopyrite-Pyrite-Epidote-Prehnite；(4) Sphalerite-Galena-Quartz-Calcite. Qia’erdunbasixi is a composite deposit with skarn type Fe mineralization and a mesothermal Cu mineralization, and has close relationship with magmatism in island arc setting.